2019
DOI: 10.2485/jhtb.28.377
|View full text |Cite
|
Sign up to set email alerts
|

Do the Presence of Mandibular Third Molar and the Occlusal Support Affect the Occurrence and the Mode of Mandibular Condylar Fractures?

Abstract: To investigate the influence of occlusal support and the presence and position of mandibular third molars on the incidence of mandibular condylar fractures. Records of 222 patients who presented with mandibular fracture at the Department of Oral and Maxillofacial Surgery, Kagawa Prefectural Central Hospital, from 2006 to 2019 were retrospectively analyzed. The following variables were investigated: age, sex, cause of fracture, the presence and state (impaction and angulation) of mandibular third molars, the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Because of the significant differences in M3 position distribution between the PR‐ and CT‐based evaluations observed in this study, the association between the mandibular condylar fracture pattern and M3 position was analyzed separately. PR‐based evaluation of the M3 position revealed no significant association between mandibular condylar fracture pattern and M3 position in the present study, consistent with Sukegawa et al 29 In contrast, a significant difference was observed between condylar intracapsular and extracapsular fractures in the distribution of the horizontal position of M3 in CT evaluations. Further comparative analysis suggested that this association between Type B and condylar base fractures was particularly prominent.…”
Section: Discussionsupporting
confidence: 90%
“…Because of the significant differences in M3 position distribution between the PR‐ and CT‐based evaluations observed in this study, the association between the mandibular condylar fracture pattern and M3 position was analyzed separately. PR‐based evaluation of the M3 position revealed no significant association between mandibular condylar fracture pattern and M3 position in the present study, consistent with Sukegawa et al 29 In contrast, a significant difference was observed between condylar intracapsular and extracapsular fractures in the distribution of the horizontal position of M3 in CT evaluations. Further comparative analysis suggested that this association between Type B and condylar base fractures was particularly prominent.…”
Section: Discussionsupporting
confidence: 90%
“…The molars are the keystones of the occlusal support. The investigations carried out by previous studies have shown that the absence of occlusion will lead to mandibular fractures 13 , 20 . The current study reported that the deficiency of occlusal support would lead to fractures on the condyle.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment requires tooth extraction surgery, extraction of the third molar is one of the most common surgical procedures worldwide. Since mandibular third molars cause a variety of complications, surgical treatment is primarily performed to treat the symptoms associated with impaction [1,2] and to prevent conditions that impair oral health, such as future dentition malocclusion [3]. Infection and neuropathy are common complications that occur after extraction of the mandibular third molars, it is known that the position of these molars in uences the occurrence of postoperative complications [4,5].…”
Section: Introductionmentioning
confidence: 99%